Synthesis of graphene-MnxOy nanocomposite as electrode sensors of profenofos. Issue 1 (May 2021) - Azis, Thamrin; Agusu, La; Kadir, L.A.; Rahmad, Muh. Resky; A. Tenri, L.O
Abstract: Synthesis and characterization of of Graphene-Mnnanocomposites as Pesticide sensor electrodes have been carried out. This study aims to determine the method for synthesizing and characterizing the products of Graphene-Mnnanocomposite synthesis. Modification of Graphene using Mn nanoparticles for profenophos analysis with cyclic voltammetry. This research using with the Modified Hummers method and the liquid phase adsorption method followed by hydrothermal. Characterization of Graphene-Mn oxide nanocomposites are displayed using XRD, SEM-EDX and FTIR. The XRD results showed that there are peaks of Mn3 O4 (30.57, 44.39), MnO2 (34.14), and MnO (39.85, 57.85, 68.94). SEM-EDX analysis reveals the surface of graphene sheets containing aggregates in shape small particles attached to graphene sheets. The results of the EDX analysis consisted of Mn 6.26%, C 53.60% and O. 15.45%. The FTIR test indicates the presence of Mn-O bonds in wave number 615.29 cm-1 and other functional groups, such as O-H, C-O, C = C, and C-H. Electrodes with the best composition at pH 6 will be used to detect pesticides profenofos with the Cyclic Voltammetry (CV) method at a scate rate of 0.05 V / s. The detection limit obtained from graphane-Mn measurements on profenofos is 0, 000667 M. and the repeatability of graphane-Mn performance is 0.0131. The age of Graphene-Mn electrodes in analyzing profenofos pesticides is 17 days. The selectivity test using Pb (NO3)2 0.1M and Phenol 0.1M disrupting compounds occurred in a negative direction.